Analyzing the Impact of Audience Sentiment on Influencer Effectiveness and Consumer Engagement in TikTok-Based Fashion Marketing - Alfin, Rita; Listiyana; Solimun; Anwar, Khoerul; Sain, Zohaib Hassan (Jurnal Aplikasi Manajemen, 2026)
The development of digital technology has changed marketing strategies, especially in the highly dynamic and competitive fashion industry. Social media has become the primary channel for reaching consumers, with TikTok a popular platform thanks to its interactive short-form video format that easily goes viral. The presence of influencers on TikTok plays an important role in building trust and encouraging consumer engagement with fashion products. This study aims to analyze the influence of audience sentiment on influencer effectiveness and consumer engagement in TikTok-based fashion marketing. The approach used is quantitative descriptive with a hybrid design. Primary data were obtained via a questionnaire, while secondary data were collected from scraped TikTok user comments. Sentiment analysis was conducted using a lexicon-based approach and validated using the Naive Bayes algorithm. The relationship between variables was tested through correlation and simple regression analysis. The results show that the quality of the audience's emotional response significantly affects the level of consumer trust and engagement with fashion promotional content. The more positive the sentiment, the higher the consumer engagement with the influencer's message. Theoretically, this study enriches the literature on digital economics and consumer behavior. In practice, the results provide insights for fashion industry players to design emotion- and data-based strategies to increase the effectiveness of digital campaigns and build consumer loyalty.